Land Rights Execution as a Pledge Object Based on MoU with PT. Pegadaian at the Office of Agrarian Affairs Ministry and National Land Agency - R Slamet Soeprijadi (Journal La Sociale, 2020)
Cooperation Agreement between the Production Director of PT Pegadaian (Persero) and the Secretary General of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency Number 352/S-00015.02/2018, Number 31/SKB-100/IV/2018. The content of the agreement is that the land certificate, especially productive land belonging to agriculture, can be used as collateral for which a mortgage is imposed in PT Pegadaian (Persero). The imposition of a certificate of land rights as collateral for a mortgage is interesting to discuss by discussing the problem of objects as collateral and the imposition and execution of collateral object rights when the debtor defaults, a conclusion is obtained as follows: Objects as collateral and the imposition, that the types of objects are distinguished between movable objects and non-movable objects. If the differentiation of objects is used as collateral, there is also a distinction. A movable object which is charged with a pledge, is required to transfer of ownership right from the giver to the recipient with the threat of cancellation if the delivery is not made. Non-movable objects are burdened with mandatory register of mortgage rights at the Land Office, the Land Office will issue a certificate of mortgage right which has the power of evidence as a court decision which has permanent legal force. Execution of the collateral object rights when the debtor defaults, if the debtor defaults does not carry out his/her obligation to pay off the debt, then at the pledge, the creditor can execute based on the provisions of Article 1150 B.W., while in the mortgage right if the debtor defaults and does not fulfill obligations voluntarily can execute according to the provisions of Article 14 UUHT (Mortgage Rights to Land and Land-Related Objects).